Transparency or Illusion? An Analysis of Financial Report Quality and Investor Confidence - Hastuti, Poppy Meilina Dian; Rahayu, Sari; Efendi, Mohamad Johan (Jurnal Informatika Ekonomi Bisnis, 2025)
This study aims to analyze the impact of financial report quality on investor confidence, focusing on four key dimensions of financial reporting quality: transparency, completeness, timeliness, and adherence to accounting standards. Data were collected through a survey of 142 respondents, consisting of investors and financial analysts. The regression analysis results show that all dimensions of financial report quality have a positive and significant impact on investor confidence. Among the four dimensions, transparency had the greatest influence, followed by completeness, timeliness, and adherence to standards. These findings suggest that transparent, complete, timely, and compliant financial reporting can enhance investor confidence, which in turn influences their investment decisions. This study provides valuable insights for companies and regulators to improve financial report quality to create a more efficient market and increase investor confidence.